IMPLEMENTASI GERAKAN LITERASI SEKOLAH UNTUK MENINGKATKAN BUDAYA MEMBACA DI SMK NEGERI 8 PONTIANAK - Susanti, Desy Indah; Aminuyati, Aminuyati; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract This study aims to determine how the application of the school literacymovement to improve the reading culture of XI Marketing class students at SMK Negeri 8 Pontianak. The research method used is descriptive research with a qualitative form of research. The data source of this research is class XI Marketing students and the data is a list of names of students who visited the library during the past year collected by library staff and interviews with school principals, deputy head of facilities and infrastructure and public relations, and class XI Marketing students. The results showed that the implementation of the school literacy movement to improve reading culture in SMK Negeri 8 Pontianak in the past year was in accordance with the guidelines for the school literacy movement and some were not yet suitable and not yet implemented at the SMK Negeri 8 Pontianak school. Factors that can support the school literacy movement to improve reading culture in SMK Negeri 8 Pontianak are facilities and infrastructure. The available facilities and infrastructure are still not optimal in accordance with good school literacy movement guidelines to support the school literacy movement.Keywords: Literacy, Reading Culture, School Literacy Movement